Adapting the World Health Organization 5 Well-Being Index for Emergency Activation and Response Planning in a US Health Care Setting - Laura E. Breeher, MD, MPH; Elizabeth H. Lees, DO, MPH; Wigdan H. Farah, MBBS, MPH; Richard D. Newcomb, MD, MPH; Caitlin M. Hainy, APRN, CNP, DNP; Byron I. Callies, Jr., CEM; Philip T. Schroeder, MS; Melanie D. Swift, MD, MPH (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2025)
Objective: To test the World Health Organization 5 Well-Being Index assessment tool as a practical way of detecting well-being changes across health care providers (HCPs) during high-consequence infectious disease (HCID) outbreaks. Participants and Methods: The study took place from October 2014 to March 2015 at a Midwest referral hospital with 2059 beds on 2 campuses. The study focused on a group of HCPs recruited for Ebola emergency response planning during the HCID outbreak in Africa. Results: Average well-being scores were worse during the initial weeks and months of the Ebola emergency response planning. Scores were lower (worse) among employees actively involved in response planning. Conclusion: Health care personnel (HCP) responding to HCID outbreaks face significant physical, cognitive, and emotional stressors Despite this, well-being assessments are not consistently integrated into emergency response plans. The World Health Organization 5 Well-Being Index assessment tool offers a practical way to detect well-being changes across HCP during HCID outbreak and response.